Drip and Sprinkler Irrigation of Dry Bean (Phaseolus vulgaris L.) in the Konya Basin, Turkey - Topak, Ramazan (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2009)
Dry bean (Phaseolus vulgaris L.) is widely planted in the Middle Anatolian Region of Turkey, especially in the Konya-Karaman-Aksaray-Nigde districts where 20% of the total dry bean growing area is located and produces 22% of the total yield. In recent years, the farmers in the Konya basin have been applying high amounts of irrigation water in order to get higher yield. This situation results in decreased ground water resources in the basin. Thus, it is critical to know the water requirement of the crop, as well as how to improve irrigation efficiency. A field experiment was conducted in Konya district (arid region) to determine the irrigation water requirement of dry bean crops under sprinkler and drip irrigation methods. Irrigation treatments were based on Class A pan evaporation. The highest yield, averaging 3132 kg ha -1, was measured in drip-irrigated plots in the irrigation treatment with full irrigation (565 mm). Maximum yields were obtained with the same amount of water in the sprinkler irrigation method compared with the drip method. In this study, bean yields were reduced by deficit in both sprinkler and drip irrigation methods. Water use of the dry bean crop ranged from 412-623 mm for sprinklerirrigated plots and 420-627 mm for drip-irrigated treatments. The highest water use efficiency (WUE) levels of 0.57 and 0.50 kg m -3 were obtained in sprinkler and drip irrigated treatments, respectively. Significant linear relationships were found between bean yield and water use for both irrigation methods. Yield response factors were calculated at 1.32 for the sprinkler method and 1.49 for the drip method.